2000
DOI: 10.1046/j.1365-2613.2000.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effect of nitric oxide during Japanese encephalitis virus infection

Abstract: The ability of Japanese encephalitis virus (JEV) and JEV-induced macrophage derived neutrophil chemotactic factor (MDF) to produce nitric oxide (NO), and the possible antiviral effect of NO during JEV infection, was investigated. Splenic macrophages of JEV infected mice produced maximum NO in vivo at day 7 post infection, and in vitro at 24 h after JEV stimulation. MDF-induced NO production was dose dependent and maximal at 60 min after MDF treatment. The response was sensitive to anti-MDF antibody treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Increased MVEV burden was detected in the serum and spleen at day 4 after infection in IFN-␥ Ϫ/Ϫ mice, and brain titers at day 8 were indistinguishable from wild-type mice, results that are consistent with our findings. Interestingly, higher mortality after MVEV infection was also observed in mice deficient in inducible nitric oxide synthase-2, an effector molecule downstream of IFN-␥ that has been reported to affect outcome after infection with JEV (56,57) and other RNA viruses (14,40). Surprisingly, our virologic data suggest that IFN-␥ has a less significant antiviral role in the CNS.…”
Section: Vol 80 2006mentioning
confidence: 53%
“…Increased MVEV burden was detected in the serum and spleen at day 4 after infection in IFN-␥ Ϫ/Ϫ mice, and brain titers at day 8 were indistinguishable from wild-type mice, results that are consistent with our findings. Interestingly, higher mortality after MVEV infection was also observed in mice deficient in inducible nitric oxide synthase-2, an effector molecule downstream of IFN-␥ that has been reported to affect outcome after infection with JEV (56,57) and other RNA viruses (14,40). Surprisingly, our virologic data suggest that IFN-␥ has a less significant antiviral role in the CNS.…”
Section: Vol 80 2006mentioning
confidence: 53%
“…In CSF the elevated level of cells and alteration of protein level indicates penetration of the blood-brain barrier. The migration of neutrophils at the site of injury may be attributed to the production of soluble macrophage-derived factor (MDF), which is one of the key mediators in the host-innate immune response during JEV infection [17]. The mild anaemia may be because a result of MDF-induced hyperferretimia in serum [18].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study has demonstrated the antiviral activity of IFN-against JEV (Hasegawa et al, 1990) and we have confirmed a critical role of IFN-in recovery from JEV infection using IFN--/-mice, which demonstrate significantly increased mortality relative to wild-type mice (Larena and Lobigs, unpublished). IFN-mediates its antiviral effect, at least in part, through induction of nitric oxide (NO) synthase (Karupiah et al, 1993) and an inhibitory effect of NO on JEV growth has been documented (Lin et al, 1997;Saxena et al, 2000). IFN-, derived from / T cells is necessary for the early control of dissemination of WNV, which is closely related to JEV (Wang et al, 2003a).…”
Section: Cellular Factors Chemokines and Cytokinesmentioning
confidence: 99%